Global burden of cutaneous melanoma in 2020 and projections to 2040 (2022)
Question What are the global incidence and mortality patterns of cutaneous melanoma in 2020, and how are they estimated to change by 2040? Findings This epidemiological assessment of global cancer data estimated that 325 000 new melanoma cases and 57 000 deaths due to melanoma occurred in 2020, with large geographic variations in incidence across countries and world regions. If 2020 rates remain stable, the global burden from melanoma is estimated to increase to 510 000 new cases and 96 000 deaths by 2040. Meaning Melanoma remains an important public health concern globally and is characterized by high incidence in fair-skinned populations of European descent and disproportionate mortality in transitioning countries.